Development of Volumetric Independent Dose Calculation System for Verification of the Treatment Plan in Image-Guided Adaptive Brachytherapy - Kang, Sang-Won; Chung, Jin-Beom; Kim, Kyeong-Hyeon; Park, Ji-Yeon; Park, Hae-Jin; Cho, Woong; Olberg, Sven; Suh, Tae Suk; Park, Justin C. (Frontiers in Oncology, 2020)
Purpose: This study aimed to develop a volumetric independent dose calculation (vIDC) system for verification of the treatment plan in image-guided adaptive brachytherapy (IGABT) and to evaluate the feasibility of the vIDC in clinical practice with simulated cases. Methods: The vIDC is based on the formalism of AAPM TG-43. Four simulated cases of cervical cancer were selected to retrospectively evaluate the dose distributions in IGABT. Some reference point-doses, such as point A, B and rectal points, were calculated by vIDC using absolute coordinate. The dose-volume was also calculated to acquire dose-volume histograms (DVHs) with grid resolutions of 1.0 × 1.0 (G1.0), 2.5 × 2.5 (G2.5) and 0.5 × 0.5 mm² (G0.5). Dosimetric parameters such as D90% and D2cc – doses covering 90% of the high-risk critical target volume (HR-CTV) and 2 cc of the organs at risk (OARs), were obtained from DVHs. D90% also converted to equivalent doses in 2 Gy fractions (EQD2) to produce the same radiobiological effect as external beam radiotherapy. In addition, D90% was obtained in two types with or without the applicator volume to confirm the effect of the applicator itself, respectively. Validation of the vIDC was also performed using gamma evaluation by comparison with Monte-Carlo simulation. Results: The average percentage difference of point-doses was less than 2.28%. The DVHs for the HR-CTV and OARs showed no significant differences between the vIDC and the TPS. Without considering the applicator volume, the D90% of the HR-CTV calculated by the vIDC decreases with a decreasing calculated dose-grid size (32.4, 5.65, and -2.20 cGy in G2.5, G1.0, and G0.5, respectively). The overall D90% is higher when considering the applicator volume. The converted D90% by EQD2 ranged from -1.29% to 1.00%. The D2cc of the OARs showed that the averaged dose deviation is less than 10 cGy regardless of the dose-grid size. Based on gamma analysis, the passing rate was 98.81% for 3%/ 3mm criteria. Conclusion: The vIDC was developed as independent dose verification system for verification of the treatment plan in IGABT. We confirmed that the vIDC is suitable for second-check dose validation of the TPS under various conditions.